2013
DOI: 10.1155/2013/353597
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effects of Orthoses on Pain in People with Lateral Epicondylalgia

Abstract: Objective. Tennis elbow is a common cause of upper limb dysfunction and a primary reason for pain at the lateral aspect of the elbow. The purpose of this study was to investigate the effects of three commonly used orthoses on pain severity. An elbow band, an elbow sleeve, and a wrist splint were assessed for their ability to reduce the level of reported pain. Method. A crossover randomized controlled trial was used. The orthoses were worn in a randomized order, and all participants were required to complete a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
9
0
3
Order By: Relevance
“…The findings demonstrated that both of the studied counterforce braces reduced pain and increased grip force in individuals with lateral epicondylitis, when assessed immediately after application. This finding is similar to other studies ( 10 , 12 , 14 , 15 ). However, our newly designed brace was significantly better at reducing pain and improving grip strength ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The findings demonstrated that both of the studied counterforce braces reduced pain and increased grip force in individuals with lateral epicondylitis, when assessed immediately after application. This finding is similar to other studies ( 10 , 12 , 14 , 15 ). However, our newly designed brace was significantly better at reducing pain and improving grip strength ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…In their study, Jafarian and colleagues used a double-layered pressure pad in the elbow strap, and found that the sleeve, which applied generalized compression around the elbow area rather than specifically to the area distal to the lateral epicondyle, increased pain-free grip strength, suggesting that specific compression may not be necessary ( 14 ). Sadeghi-Demneh and Jafarian compared the immediate results of an elbow counterforce band, an elbow counterforce sleeve, and a wrist splint with a placebo, and found that the elbow counterforce orthosis was more effective than the wrist splints ( 15 ). These authors reported that applying a counterforce orthosis at the elbow (either a strap or sleeve) improved pain-free grip strength in individuals with lateral epicondylitis when tested immediately after application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar comparison by Altan and colleagues demonstrated statistically significant improved pain ratings with rest and movement at 2 and 6 weeks following treatment with a wrist splint [13]. Sadeghi-Demneh evaluated the immediate effect of various orthoses on pain severity associated with lateral epicondylitis and found that a wrist splint offered statistically significant improvement in pain levels compared to placebo [23]. The reason for the immediate pain relief is hypothesized to be due to decreased activity of the involved musculotendinous units that alleviates dynamic compression at their origin.…”
Section: Discussionmentioning
confidence: 76%